Development of implantation substrates for the collection of radionuclides of medical interest produced via ISOL technique at INFN-LNL. (September 2021) - Ballan, M.; Vettorato, E.; Morselli, L.; Tosato, M.; Nardella, S.; Borgna, F.; Corradetti, S.; Monetti, A.; Lunardon, M.; Zenoni, A.; Di Marco, V.; Realdon, N.; et al.
Abstract: Accelerator-based techniques with electromagnetic mass separation are considered among the most innovative and promising strategies to produce non-conventional radionuclides for nuclear medicine. Such approach was successfully used at CERN, where the dedicated MEDICIS facility was built, and at TRIUMF, where the ISAC radioactive beam facility was used to produce unconventional α-emitters. In such framework, the Legnaro National Laboratories of the Italian Institute of Nuclear Physics (INFN-LNL) proposed the ISOLPHARM project (ISOL technique for radioPHARMaceuticals), which will exploit radionuclides producible with the SPES (Selective Production of Exotic Species) ISOL (Isotope Separation On-Line) facility to develop novel radiopharmaceuticals. The ISOL technique utilizes the irradiation with a primary beam of particles/nuclei of a production target where radionuclides are produced. A radioactive ion beam is subsequently extracted from the production target unit, and transported up to an analyzing magnet, where non-isobaric contaminants are filtered out. The so-obtained purified radioactive beam is dumped onto an implantation substrate, referred as collection target. Then, the desired nuclides can be chemically harvested from the collected isobars, and the isotopically pure atom collection can be employed to radiolabel high specific activity radiopharmaceuticals. Metallic deposition targets in the form of coated metal foils were mostly used at TRIUMF and CERN. At ISOLPHARM, a different approach is under investigation which foresees the use of soluble cold-pressed collection targets, possibly facilitating the chemical purification process of the collected radionuclides. In this study, the production and characterization of some of the ISOLPHARM collection targets is presented, in particular, soluble salts (NaCl and NaNO3) and organic materials widely used for pharmaceutical tablets production are considered. All such materials proved to be potentially suitable as collection targets, since solid samples were easily produced and resulted compatible with the vacuum conditions required for the ion implantation process. Furthermore, some of the selected substrates were used for proof-of-concept deposition tests with stable silver, to prove their suitability as ISOLPHARM deposition substrates for silver-111, a promising candidate for radiotherapy. Such tests highlighted possible scenarios useful for the development of new alternative materials, as the use of insoluble organic targets. Highlights: ISOL based techniques for the production of medical radionuclides require the use of an implantation target. Generally, implantation targets are metallic foil, ISOLPHARM at INFN-LNL proposes saline or organic substrates. NaCl, NaNO3, cellulosic and dextrates substrates were produced by direct compression. All samples were characterized in terms of density, mechanical strength, disaggregation and vacuum compatibility. Implantation depth calculations and tests with the deposition of Ag  +  ions were performed.